The Optimization of NaOH and Cassava Starch Concentration on The Quality of Art Paper from Banana Leaves - Sucipto, Sucipto; Wijana, Susinggih; Wahyuningtyas, Erly (Fakultas Teknologi Pertanian Universitas Brawijaya, 2009)
The main purpose of this research was to find out the optimum concentration of NaOH and cassava starch on the production of art paper from the banana leaves. The central composite design in Response Surface Methodology was used with two factors i.e. NaOH (b/v) and cassava starch concentration, and 5 times repetition at central point. The data was analyzed using design expert DX7.0.3, the organoleptic test used t-test, and financial analysis was conducted on HPP, BEP, PP, and NPV. The result showed that NaOH and cassava starch concentration affected the tearing strength value and tensile strength. The optimum process reached on NaOH concentration of 0.50% b/v and the cassava starch concentration of 0.39% b/v. The organoleptic test showed that most of the panelist preferred paper appearance and the thickness. By the investment of Rp. 45.9198.419,00 and 500 sheets production capacity per day, the HPP value was Rp. 427,92. With the selling price of Rp. 599,06 per sheet, the financial analysis was as followed: BEP was 47.514,38 sheet that equal to Rp. 28.465.353,32 or 32.99%; PP was 2 years 11 month and 6 days, and NPV was Rp. 56.474.249,06.Keywords : art paper, banana leaves, optimization, financial analysis